Effects of education and exercise on pain, depression and quality of life in patients diagnosed with Fibromyalgia - Demirbag, Canan; Oguzoncul, Ferdane (Drunpp-Sarajevo, 2012)
Objective: Fibromyalgia syndrome is a very common rheumatological disorder and there are various treatment modalities. The aim of the present study was to investigate the effect of education and exercise programs in the treatment of patients with fibromyalgia syndrome. Materials and Methods: One hundred-two patients who were diagnosed with fibromyalgia syndrome according to the American College of Rheumatology criteria were included the study. Their ages ranged between 19 and 58 years. The patients were assigned into two groups: the intervention group (n= 51) who received education and exercise programs at home and the control group (n= 51) who did not receive these programs. All of the patients were asked to complete the Beck depression inventory to evaluate depression, visual analogue scale to evaluate the level of pain, and fibromyalgia impact questionnaire to assess the quality of life score. Results: After the programs, there was a significant difference between the scores of Beck depression inventory, visual analogue scale, and fibromyalgia impact questionnaire in the intervention group (p < 0.05, for each). Furthermore, there was an improvement in between the scores of Beck depression inventory, visual analogue scale, and fibromyalgia impact questionnaire in the intervention group compared to the control group (p < 0.05, for each). Conclusion: Patients with fibromyalgia syndrome mostly complained about the pain and the difficulty in the daily living activities. The present study showed that education and exercise programs at home had positive effect on pain, quality of life, and depression in patients with fibromyalgia syndrome.
Keywords: Fibromyalgia; depression; education; exercise; quality of life